Preoperative neutrophil to lymphocyte ratio as a predictor of the severity of acute appendicitis - Bhattarai, Abhishek; Devkota, Pragya; Bhattarai, Suraj Raj; Karna, Nitesh Kumar; Shrestha, Anup; Tamarakar, Kishor Kumar; Neupane, Harish Chandra; Timalsina, Santosh (Journal of Chitwan Medical College, 2021)
Background: Neutrophil to lymphocyte ratio (NLR) is one of the tools to differentiate complicated and uncomplicated acute appendicitis (AA) preoperatively. However there is a considerable difference in the cutoff values of NLR in different studies. This study aimed to establish a cutoff value of NLR to distinguish complicated AA from uncomplicated AA preoperatively at our center. Methods: This was a prospective observational study conducted over 2 years from January 2017 to December 2019 in the department of surgery, Chitwan Medical College Bharatpur. Patients with a provisional diagnosis of AA and undergoing appendectomy were included in the study. The difference in NLR between the two groups was compared by Mann-Whitney U-test. The predictive ability of NLR was estimated by the receiver operating characteristic (ROC) curve analysis. Results: One hundred eighty-eight patients were included in the study, 112 patients were males and 76 were females. Among them, 29.2% (n=55) were complicated AA. Median NLR was significantly higher in the complicated AA group compared to the uncomplicated group (6.90 vs 4.27, P <0.001). On ROC analysis, the predictive ability of NLR for complicated AA was acceptable (AUC: 0.705, p <0.001). The optimal cut-off value of NLR to predict complicated acute appendicitis was 4.77, with sensitivity and specificity 74.5% and 65.4% respectively. Conclusions: NLR ≥ 4.77 can be a useful adjunct in predicting complicated AA preoperatively. But because of poor sensitivity and specificity, a lower value does not exclude complicated AA. and therefore other biochemical and radiological parameters have to be taken into consideration.